Detecting vinyl chloride by phytoscreening in the shallow critical zone at sites with potential human exposure. (1st October 2022) - Filippini, Maria; Leoncini, Carlotta; Luchetti, Lucina; Emiliani, Renata; Fabbrizi, Emanuela; Gargini, Alessandro
Abstract: Chlorinated ethene (CE) contaminants are widespread in groundwater, and the occurrence of vinyl chloride (VC), among others, is a well-known issue due to its mobility, persistence, and carcinogenicity. Human exposure to VC may occur through inhalation after soil vapor intrusion into buildings at sites with shallow underground contamination. Soil vapor intrusion risk is traditionally assessed through indoor air and sub-slab sampling (direct evidence) or soil gas and groundwater surveys (indirect evidence). Phytoscreening (sampling and analysis of tree trunk matrices) was proven as a cost-effective alternative technique to indirectly detect shallow underground contamination by higher chlorinated ethenes and subsequent vapor intrusion risk. However, the technique has appeared barely capable to screen for the lower chlorinated VC, likely due to its fugacity and aerobic bio-degradability, with only one literature record to date showing successful detection in trees. We applied phytoscreening at two sites with severe CE contamination nearby residential buildings caused by illegal dumping of chlorinated pitches from petrochemical productions. The two sites show variable amounts of VC in the shallow groundwater (1e2 to 1e4 μg/L), posing potential sanitary risk issues. Former soil gas surveys did not detect VC in the vadose zone. At both sites, we sampled trunk micro-cores and trunk gas from poplar trees close to contaminated piezometers in different seasons. VC was detected in several instances, disproving the shared literature assumption of the inefficacy of phytoscreening towards this compound. Factors influencing the detectability of VC and other CEs in trees were analyzed through linear regressions. Two different conceptual models were proposed to explain the effective uptake of VC by trees at the two sites, i.e., direct uptake of contaminated groundwater at the first site and uptake of VC from an anoxic vadose zone at the second site. In planta reductive dechlorination of CEs is not expected based on current literature knowledge. Thus, the detection of VC in trunks would indicate its occurrence in the shallow underground, suggesting higher screening effectiveness of phytoscreening compared to soil gas; this has implications for indirect vapor intrusion risk assessment. Highlights: Populus Nigra trees detect shallow underground contamination by vinyl chloride. The efficacy of phytoscreening for vinyl chloride depends on site-specific features. Phytoscreening is more effective than soil gas to detect underground vinyl chloride.